PENGARUH MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KECAMATAN SESAYAP HILIR KABUPATEN TANA TIDUNG - Samsul, Syahril (PREDIKSI, 2014)
The purpose of this study is, to determine the effect of motivation on employee performance. Samples were taken by 37 respondents. Research conducted by this research group includes verification (causalitas). Analysis of the data used is the method of analysis of KoeficientCorrelation of Product Moment (pearson).Based on these results it can be concluded that: 1) Motivation is a condition that affects arouse, direct and maintain behaviors associated with performance.Meanwhile Work Achievement is the result achieved by the size of a person who applies for the job in question. 2) Product Moment Correlation coefficient was r = generated 0.568. Motivation variable has a positive relationship with the variable Employee Job Performance.The results of the comparison between the empirical value of r (count) with the theoretical value of r (table) in the table of critical prices for product moment r, ie r (count) = 0.568; r (tab) = 0.325 at the 0.05 level for n = 37.This means that there is a positive relationship between the variables with the variable Achievement Motivation Works employees. 3) Testing hypotheses using t-test, can result in t (hit) = 3.817,shows that t is greater than t table at the 0.05 level, ie t (hit) = 3.817> t (tab) = 1.690, meaning there is a positive and significant effect of the variable Motivation on Employee Job Performance variables.